Esophageal sutures: Comparative experimental study - Camaño, Mario; Danni, Doris; Herdt, Emilio; Grancelli, Luis; Camaño, Jorge (Cirugía del Uruguay, 1991)
30 dogs were operated on in order to make a comparative study of esophagical sutures. lt is obseved that diferent techniques are efective for establishing continuity, but that anastomosis varíes according to the type of suture employed. The fact that concepts and techniques for gastrointestinal sutures can be applied to esophagus is confirmed and the importance of submucosa and unimpotance of mucosa is emphasized. Excellent results were obained with extramucous sutures and Gambee stitches.